2022
DOI: 10.1161/circimaging.122.014158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex and Cardiovascular Risk Factors on Myocardial T1, Extracellular Volume Fraction, and T2 at 3 Tesla: Results From the Population-Based, Hamburg City Health Study

Abstract: Background: Reliable reference intervals are crucial for clinical application of myocardial T1 and T2 mapping cardiovascular magnetic resonance imaging. This study evaluated the impact of sex and cardiovascular risk factors on myocardial T1, extracellular volume fraction (ECV), and T2 at 3T in the population-based HCHS (Hamburg City Health Study). Methods: The final study sample consisted of 1576 consecutive HCHS participants between 46 and 78 years wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 51 publications
(123 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, some of the more recent cardiovascular risk scores include inflammatory markers like CRP (C-reactive protein) which increases their prognostic value. Cavus et al 3 do not report any association with inflammatory markers, although myocardial fibrosis quantified by T1 and ECV have been linked to systemic inflammation markers like CRP. 8 In MESA, investigators found native T1 to be slightly elevated in participants treated for diabetes, and ECV was higher in smokers.…”
Section: See Article By Cavus Et Almentioning
confidence: 92%
See 4 more Smart Citations
“…Furthermore, some of the more recent cardiovascular risk scores include inflammatory markers like CRP (C-reactive protein) which increases their prognostic value. Cavus et al 3 do not report any association with inflammatory markers, although myocardial fibrosis quantified by T1 and ECV have been linked to systemic inflammation markers like CRP. 8 In MESA, investigators found native T1 to be slightly elevated in participants treated for diabetes, and ECV was higher in smokers.…”
Section: See Article By Cavus Et Almentioning
confidence: 92%
“…More than 80% of the studies included in the metaanalysis had groups of healthy controls with 50 or fewer subjects, with a median of 20 subjects for studies at 3 Tesla. The study by Cavus et al 3 with 1576 participants all scanned at 3 Tesla, provides, therefore, valuable data for T1 and T2 reference ranges for a much larger cohort.…”
Section: See Article By Cavus Et Almentioning
confidence: 99%
See 3 more Smart Citations